2020
DOI: 10.17159/wsa/2019.v46.i1.7892
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and potential of separate anaerobic digestion of municipal sewage sludge fractions

Abstract: Feasibility of the separate anaerobic stabilization of primary (PS) and secondary (SS) sludge fractions produced in municipal wastewater treatment plants (WWTP) was studied at volatile loading rates (VLR) of 0.57–2.05 and 0.27–0.57 kg VS/(m3∙d) for PS and SS, respectively, corresponding to 16–30 and 14–28 d of hydraulic retention time (HRT). Laboratory-scale semi-continuous anaerobic reactors were operated at 35°C.  The operational performance and quality of the final stabilized sludge were monitored. PS and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…The differences were not significant at every HRT (P > 0.05). Similar results have been reported in previous studies; one showed that η VS in primary sludge digestion reached a stable 52% at HRT = 22 days (1.5 g VS/L•d), 23 and one showed a decrease in η VS from 24.1% at HRT = 20 days to 28.0% at HRT = 15 days and 22.6% at HRT = 10 days in anaerobic sludge digestion with Fe-reducing bacteria. 1 η VS was stable at HRT > 15 days in both digesters, as was also reported in a previous study.…”
Section: Volatile Solidssupporting
confidence: 91%
“…The differences were not significant at every HRT (P > 0.05). Similar results have been reported in previous studies; one showed that η VS in primary sludge digestion reached a stable 52% at HRT = 22 days (1.5 g VS/L•d), 23 and one showed a decrease in η VS from 24.1% at HRT = 20 days to 28.0% at HRT = 15 days and 22.6% at HRT = 10 days in anaerobic sludge digestion with Fe-reducing bacteria. 1 η VS was stable at HRT > 15 days in both digesters, as was also reported in a previous study.…”
Section: Volatile Solidssupporting
confidence: 91%